Association among resilience, post-traumatic stress disorder, and somatization in frontline healthcare workers in COVID-19: The mediating role of perceived stress - Li, Minjie; Yu, Xingfeng; Wang, Dan; Wang, Ying; Yao, Lipei; Ma, Yunmiao; Liu, Xiaomei; Zhang, Yulian (Frontiers in Psychiatry, 2022)
Background: Frontline healthcare workers were at a high risk of infection and developing mental health problems during the outbreak of coronavirus disease 2019 (COVID-19). It is important to monitor the symptoms of post-traumatic stress disorder (PTSD) and somatization among frontline healthcare workers in China. Aim: This study aimed to investigate PTSD, somatization, resilience, and perceived stress among frontline healthcare workers fighting against COVID-19 and examine the mediating effects of perceived stress on resilience in both PTSD and somatization. Methods: The study was conducted from December 2021 to February 2022 through an online survey of frontline healthcare workers fighting against COVID-19. The survey included questions regarding socio-demographic information, resilience (10-item Conner–Davidson Resilience Scale, CD-RISC-10), perceived stress (14-item Perceived Stress Scale), PTSD (Post-traumatic Stress Disorder Checklist-Civilian Version, PCL-C), and somatization (Symptom Checklist-90). The PROCESS macro for SPSS was used to examine the mediating effects of perceived stress. Results: Approximately 14.9% of healthcare workers had possible PTSD (PCL-C score of ≥ 44), and 41.04% of the workers had low resilience (CD-RISC-10 score of ≤ 25.5). Approximately 54.05% of healthcare workers were symptomatic, and 14.7% had a moderate or higher degree of somatization with sleep-related problems as the most common symptom. Perceived stress was negatively correlated with resilience (r = -0.527, p < 0.001) and positively correlated with PTSD (r = 0.505, p < 0.001) and somatization (r = 0.361, p < 0.001). In addition, perceived stress mediated the relationship between resilience and PTSD (indirect b = -0.382; bootstrapped confidence interval, -0.454, -0.319) and somatization (indirect effect b = -0.159; bootstrapped confidence interval, -0.199, -0.123). Conclusions: The prevalence of PTSD and somatic symptoms indicates that the mental health of frontline healthcare workers deserves more attention. Resilience is negatively associated with PTSD and somatization, and the relationship among resilience, PTSD, and somatization is mediated by perceived stress. Strategies for reducing perceived stress and increasing resilience may help to prevent and alleviate PTSD and somatization.